'Een mooie mengelmoes' Meertaligheid in de Gouden Eeuw - van Oostendorp , Marc (Amsterdam University Press, 2019)
The linguistic relality in the Netherlands during the Golden Age was in fact one of multilingualism: so many languages and dialects were used. Nicoline van der Sijs and Marc van Oostendorp show how the emergence of the Dutch language can only be understood against this multilinguistic background.